The Charm of Kanigoro Beach: Student Tourism Trends and Social Media Effects - Intan Nurmala Fadin, Delfyan; Oktaviani Gustiarti, Putrisari; Khairune Nisa, An Nuur (Ann Publisher, 2023)
This study aims to describe the charm of Kanigoro Beach, a tourist trend for students, and theeffect of social media. Kanigoro is located on the coast of Gunungkidul and has beautiful beach potential,namely Ngrenehan, Ngobaran, and Nguyahan (3N). However, there is no public transportation availabledirectly to access the location of this Kanigoro beach area. The TikTok social media application is used inthis analysis because the growth rate of TikTok users in Indonesia is increasing rapidly. Recognizing thetremendous potential but also the challenges faced, strategic steps need to be taken to improveinfrastructure, environmental hygiene, accessibility, and tourism management holistically. Increasingcooperation between related parties, involving local communities in sustainable management, andimproving transportation facilities and accessibility can be critical first steps to optimize the tourismpotential of 3N Beach in the Kanigoro Area.